Exploring Professional Commitment and Passion Among Norwegian High School Teachers - Eriksen, Harald; Elstad, Eyvind (Professions and professionalism, 2025)
High school teachers’ professional commitment and passion are about being dedicated and unwavering in their pursuit of teaching excellence. This study aims to explore the antecedents of Norwegian high school teachers’ professional passion. We investigated three factors—relational trust, teachers’ affective commitment to the school organisation, and teachers’ instructional self-efficacy—by conducting a survey of 246 Norwegian high school teachers and using structural equation modelling. Our findings reveal a positive relationship between teachers’ self-efficacy and teachers’ professional passion, as well as a positive relationship between trust among teachers and their passion. Further, affective commitment to the school organisation is indirectly related to teacher passion via relational trust between teachers. We thus conclude that both teacher efficacy and trust between teachers are directly related to teachers’ passion, while teachers’ affective commitment to the school is indirectly related via relational trust. Implications for practice and further research are discussed.